2013
DOI: 10.1002/pen.23765
|View full text |Cite
|
Sign up to set email alerts
|

Improved tensile strength and thermal stability of thermoplastic carbon fiber fabric composites by heat induced crystallization of in situ polymerizable cyclic butylene terephthalate oligomers

Abstract: Thermoplastic carbon fiber fabric reinforced composites (CFFRCs) were prepared using a novel fast manufacturing process with a low viscosity polymerizable cyclic butylene terephthalate (CBT) resin. Structure and properties of the composites altered by thermal annealing were investigated to develop appropriate post processing of the CFFRCs for fast production and lowering the processing cost. Annealing at 200°C for 120 min resulted in improved mechanical properties and thermal stability of the polymerized CBT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…When engineered thermoplastics are applied to CFRP composites, the high melt viscosity of thermoplastic resins may cause a critical problem by keeping the continuous carbon structures from being impregnated 7 , 8 . A recent method proposed to make up for this problem by using the ring-opening, polymerizable and low-viscosity cyclic butylene terephthalate (CBT) resin, which is a macrocyclic oligomer, for the fabrication of thermoplastic CFRP composites 9 , 10 . When heated above 150 °C, CBT molecules melt and impregnate CF fabrics with a low viscosity of 0.02 Pa·s.…”
Section: Introductionmentioning
confidence: 99%
“…When engineered thermoplastics are applied to CFRP composites, the high melt viscosity of thermoplastic resins may cause a critical problem by keeping the continuous carbon structures from being impregnated 7 , 8 . A recent method proposed to make up for this problem by using the ring-opening, polymerizable and low-viscosity cyclic butylene terephthalate (CBT) resin, which is a macrocyclic oligomer, for the fabrication of thermoplastic CFRP composites 9 , 10 . When heated above 150 °C, CBT molecules melt and impregnate CF fabrics with a low viscosity of 0.02 Pa·s.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous fiber-reinforced pCBT composites containing CF 83,91 or carbon fabric 26,85,86 have been investigated by many researchers. Different experimental conditions for composite manufacturing processes based on melt blending, compression molding and vacuum infusion were proposed.…”
Section: Traditional Fiber-reinforced Compositesmentioning
confidence: 99%
“…In a follow-up work, 207 Kim et al 204 suggested a novel fast manufacturing process using high-speed processing at 250 °C for 2 min. Structure and properties of the composites were altered by thermal annealing and the mechanical properties as well as thermal stability were improved as the remaining CBT oligomers were polymerized further.…”
Section: Composites With Carbon Fibresmentioning
confidence: 99%